2019
DOI: 10.1111/1462-2920.14620
|View full text |Cite
|
Sign up to set email alerts
|

Differential protein expression during growth on linear versus branched alkanes in the obligate marine hydrocarbon‐degrading bacterium Alcanivorax borkumensis SK2T

Abstract: Summary Alcanivorax borkumensis SK2T is an important obligate hydrocarbonoclastic bacterium (OHCB) that can dominate microbial communities following marine oil spills. It possesses the ability to degrade branched alkanes which provides it a competitive advantage over many other marine alkane degraders that can only degrade linear alkanes. We used LC–MS/MS shotgun proteomics to identify proteins involved in aerobic alkane degradation during growth on linear (n‐C14) or branched (pristane) alkanes. During growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 75 publications
1
27
0
Order By: Relevance
“…The n -hexadecane metabolism of Marinobacter sp. TT1 appears relatively analogous to the alkane metabolism of other marine alkane degraders [ 49 , 50 , 51 ], with our results suggesting important roles for the AupAB, AlkB2, and cytochrome P450 homologues and a number of involved dehydrogenases. The AupA homologue likely enables strain TT1 to take up n -hexadecane from the outer membrane, with the AupB homologue guiding the alkane to the inner membrane, where the terminal oxidation machinery is located [ 46 ].…”
Section: Discussionsupporting
confidence: 68%
“…The n -hexadecane metabolism of Marinobacter sp. TT1 appears relatively analogous to the alkane metabolism of other marine alkane degraders [ 49 , 50 , 51 ], with our results suggesting important roles for the AupAB, AlkB2, and cytochrome P450 homologues and a number of involved dehydrogenases. The AupA homologue likely enables strain TT1 to take up n -hexadecane from the outer membrane, with the AupB homologue guiding the alkane to the inner membrane, where the terminal oxidation machinery is located [ 46 ].…”
Section: Discussionsupporting
confidence: 68%
“…Because its isolation and characterization, the genus Alcanivorax has become a reference of marine oildegradation (Yakimov et al, 1998;de Lorenzo, 2006;Schneiker et al, 2006;Gregson et al, 2019). Although Alcanivorax spp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of oil-contaminated sediment ( Coulon et al, 2012 ) and seawater ( Teramoto et al, 2013 ) observed Oleibacter and Alcanivorax in similar abundances, in line with our observations. However, in seawater-based laboratory experiments Thalassolituus has been observed to outcompete other alkane-degraders such as Alcanivorax ( McKew et al, 2007 ), through its use of medium- and long-chained alkanes ( Gregson et al, 2019 ); this was not observed in the sediment samples collected from the Agia Zoni II oil-spill, whereby Alcanivorax was in greater abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, this persistence could be due to the low levels of branched alkanes, such as pristane and phytane, observed within the sediments in the months following September. Unlike most OHCB, certain species of Alcanivorax can use branched alkanes, for example, A. borkumensis SK2T (Yakimov et al, 1998;Gregson et al, 2019), A. dieselolei B-5 (Liu et al, 2011), and A. hongdengensis A-11-3 (Wang and Shao, 2012).…”
Section: Ecology Of Obligate Hydrocarbonoclastic Bacteriamentioning
confidence: 99%